Respuesta :

While it's pretty obvious to most of us that


-13x=90-2y

-6x=48-2y


is a system of linear equations, it'd be well to include that info plus the instructions "solve this system of linear equations."


Subtract the 2nd equation from the first:


-13x=90-2y

+6x=-48+2y

-----------------------

-7x = 42. Then x = -42/7, or x = 6.


Now subst. 6 for x in either one of the given equations. Suppose we use the 2nd equation:


-6x=48-2y


Then -6(6)=48-2y, or -36 = 48 - 2y, or 2y = 48+ 36 = 84. Then y = 42.


The solution is (6, 42).

Otras preguntas